Endothelial damage arising from high salt hypertension is elucidated by vascular bed systematic profiling - Vinaiphat, Arada (2024)
Background: Considerable evidence links dietary salt intake with the development of hypertension, left ventricular hypertrophy, and increased risk of stroke and coronary heart disease. Despite extensive epidemiological and basic science interrogation of the relationship between high salt (HS) intake and blood pressure, it remains unclear how HS impacts endothelial cell (EC) and vascular structure in vivo. This study aims to elucidate HS-induced vascular pathology using a differential systemic decellularization in vivo approach. Methods: We performed systematic molecular characterization of the endothelial glycocalyx and EC proteomes in mice with HS (8%) diet-induced hypertension versus healthy control animals. Isolation of eGC and EC compartments was achieved using differential systemic decellularization in vivo methodology. Altered protein expression in hypertensive compared to normal mice was characterized by liquid chromatography tandem mass spectrometry. Proteomic results were validated using functional assays, microscopic imaging, and histopathologic evaluation. Results: Proteomic analysis revealed a significant downregulation of eGC and associated proteins in HS diet-induced hypertensive mice (among 1696 proteins identified in this group, 723 were markedly decreased in abundance, while only 168 were increased in abundance. Bioinformatic analysis indicated substantial derangement of the eGC layer, which was subsequently confirmed by fluorescent and electron microscopy assessment of vessel damage ex vivo. In the EC fraction, HS-induced hypertension significantly altered protein mediators of contractility, metabolism, mechanotransduction, renal function, and the coagulation cascade. In particular, we observed dysregulation of integrin subunits α2, α2b, and α5, which was associated with arterial wall inflammation and substantial infiltration of CD68+ monocyte-macrophages. Consequently, HS-induced hypertensive mice also displayed reduced vascular integrity of multiple organs including lungs, kidneys, and heart. Conclusions: These findings provide novel molecular insight into HS-induced structural changes in eGC and EC composition that may increase cardiovascular risk and potentially guide the development of new diagnostics and therapeutic interventions.